Diabetes, metformin and incidence of and death from invasive cancer in postmenopausal women: Results from the women's health initiative. Issue 8 (15th December 2015) - Gong, Zhihong; Aragaki, Aaron K.; Chlebowski, Rowan T.; Manson, JoAnn E.; Rohan, Thomas E.; Chen, Chu; Vitolins, Mara Z.; Tinker, Lesley F.; LeBlanc, Erin S.; Kuller, Lewis H.; Hou, Lifang; LaMonte, Michael J.; et al.
Abstract : Findings from studies of metformin use with risk of cancer incidence and outcome provide mixed results; with few studies examined associations by recency of diabetes diagnosis or duration of medication use. Thus, in the Women's Health Initiative, we examined these associations and further explored whether associations differ by recency of diabetes and duration of metformin use. Cox regression models were used to estimate hazard ratios (HR) and their 95% confidence intervals. Diabetes was associated with higher risk of total invasive cancer (HR, 1.13; p < 0.001) and of several site‐specific cancers (HR, 1.2–1.4, and up to over twofold). Diabetes was also associated with higher risk of death from cancer (HR, 1.46; p < 0.001). There was no overall difference in cancer incidence by diabetes therapy ( p = 0.66). However, there was a lower risk of death from cancer for metformin users, compared to users of other medications, relative to women without diabetes, overall (HRs, 1.08 vs . 1.45; p = 0.007) and for breast cancer (HRs, 0.50 vs . 1.29; p = 0.05). Results also suggested that lower cancer risk associated with metformin may be evident only for a longer duration of use in certain cancer sites or subgroup populations. We provide further evidence that postmenopausal women with diabetes are at higher risk of invasive cancer and cancer death. Metformin users, particularly long‐term users, may be at lower risk of developing certain cancers and dying from cancer, compared to users of other anti‐diabetes medications. Future studies are needed to determine the long‐term effect of metformin in cancer risk and survival from cancer. Abstract : What's new? Insulin resistance and excess circulating insulin are likely suspects underlying the link between diabetes mellitus and cancer. Hence, metformin therapy, which sensitizes tissues to insulin, may have a role in the prevention or management of diabetes‐associated cancer. Here, among diabetic postmenopausal women, long‐term metformin use was associated with a reduced risk of death from cancer. This benefit was not observed among women who took other antidiabetes medications. Overall cancer risk was found to be similar across diabetes therapies, though possible metformin‐mediated anticancer effects may become apparent only after long duration of use.